1986
DOI: 10.1192/bjp.149.1.125
|View full text |Cite
|
Sign up to set email alerts
|

Seasons of Birth and Sub-Types of Schizophrenia

Abstract: Inhibition of prostaglandin synthesis increases plasma lithium levels. Clinical Research, 26, 291A.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Some studies have found an association between the peak of birth seasonality and certain clinical forms, mainly disorganized subtype [ 32 ], paranoid subtype [ 33 ] or with pronounced negative symptomatology [ 34 ]. In addition, patients with schizophrenia who were exposed to an elevated risk of influenza infection during pregnancy are more likely to be single, which could indicate poorer social adjustment [ 35 ], and with the disorganized clinical subtype [ 18 ].…”
Section: The Neurodevelopmental Hypothesis Applied To Negative Symptomentioning
confidence: 99%
“…Some studies have found an association between the peak of birth seasonality and certain clinical forms, mainly disorganized subtype [ 32 ], paranoid subtype [ 33 ] or with pronounced negative symptomatology [ 34 ]. In addition, patients with schizophrenia who were exposed to an elevated risk of influenza infection during pregnancy are more likely to be single, which could indicate poorer social adjustment [ 35 ], and with the disorganized clinical subtype [ 18 ].…”
Section: The Neurodevelopmental Hypothesis Applied To Negative Symptomentioning
confidence: 99%
“…For example, Torrey et al (1977) divided their sample of schizophrenics into paranoid and "process" (includes simple, hebephrenic, catatonic, and chronic undifferentiated schizophrenia) subgroups, and found no significant differences with regard to seasonality of birth. On the other hand, a study by Hsieh et al (1986) revealed that male paranoid schizophrenics showed a significant larger proportion of births than controls during the first quarter of the year. Thus it seems clear that further investigation is needed to elucidate the parameters of this phenomenon.…”
Section: Discussionmentioning
confidence: 96%
“…Miller reviewed the results of 43 studies, and there are many more recent studies (e.g., Baron & Gruen, 1988;Dereeef, Mukherjee, Bilder, & Schnur, 1988;Fa~nanas, Marti-Tusquets, & Bertranpetit, 1989;Hsieh, Khan, & Atwal, 1986;Kendell & Adams, 1991;Kendell & Kemp, 1987;Lo, 1986;Machon, Mednick, & Schulsinger, 1983;Newman & Bland, 1988;O'Callaghan et al, 1991;Woodard & Feldman, 1990). The results of these studies can be generally summarized as follows:…”
Section: Previous Studiesmentioning
confidence: 99%
See 1 more Smart Citation